1990
DOI: 10.1038/bjc.1990.125
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant gamma interferon provokes resistance of human breast cancer cells to spontaneous and IL-2 activated non-MHC restricted cytotoxicity

Abstract: Summary Natural and lymphokine activated killer cells (NK and LAK)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

1991
1991
1998
1998

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 28 publications
1
0
1
Order By: Relevance
“…The increase in NK cell-mediated lysis of melanoma cells induced by anti-HLA class I MAb parallels similar results obtained with human T cell lymphomas, breast carcinoma cells (34) and lung small cell carcinomas (5) and with mouse thymoma cells (26). On the other hand, these results are at variance with the lack of effect of anti-MHC class I antibodies on the NK cell-mediated lysis ofhuman (5) and mouse (35) melanoma cells and of human lymphoblastoid cells (27).…”
Section: Methodssupporting
confidence: 70%
See 1 more Smart Citation
“…The increase in NK cell-mediated lysis of melanoma cells induced by anti-HLA class I MAb parallels similar results obtained with human T cell lymphomas, breast carcinoma cells (34) and lung small cell carcinomas (5) and with mouse thymoma cells (26). On the other hand, these results are at variance with the lack of effect of anti-MHC class I antibodies on the NK cell-mediated lysis ofhuman (5) and mouse (35) melanoma cells and of human lymphoblastoid cells (27).…”
Section: Methodssupporting
confidence: 70%
“…On the other hand, these results are at variance with the lack of effect of anti-MHC class I antibodies on the NK cell-mediated lysis ofhuman (5) and mouse (35) melanoma cells and of human lymphoblastoid cells (27). Furthermore, our results differ from those in the literature in two aspects; in Lobo and Spencer's (5) experiments, only target cells which do not express HLA class II antigens were susceptible to increase in NK cell-mediated lysis by anti-HLA class I antibodies, whereas in our studies, the phenomenon was observed with a melanoma cell line which expresses HLA (34), the whole IgG of the anti-HLA class I MNAb tested enhanced the extent of NK cellmediated lysis, whereas the F(ab')2 fragments did not, therefore suggesting that the increase mediated by anti-HLA class I MAb may reflect an ADCC phenomenon. On the other hand, in our experiments, the whole IgG of anti-HLA class I MAb were as effective as F(ab')2 fragments in enhancing NK cell-mediated lysis of melanoma cells FO-lC and FO-lH.…”
Section: Methodscontrasting
confidence: 56%